Perkembangan Perusahaan Fintech Indonesia: Sebuah Tinjauan Produk, Akad dan Performa pada ALAMI Sharia - Muhammad Fuad Adisaputra; M Izdiyan Muttaqien (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Islamic fintech industry provides solutions for SMEs who need funding access besides banks. One of the Islamic fintechs contributing to the economy in Indonesia is PT. Alami Fintek Sharia or commonly known as ALAMI Sharia. This article attempts to describe the products and contracts used by ALAMI Sharia and its financial condition from 2019 to 2021. The method used is descriptive analysis of data obtained from primary and secondary data sources. The research results show that ALAMI has 3 types of products, namely invoice financing, purchase order financing, and community-based financing. In these products, the contracts used are a combination of Wakalah bil Ujroh, Hawalah bil Ujroh, Qardh, Murabahah, and Musyarakah. On the other hand, ALAMI Sharia has shown good performance in 2021 by recording several financial ratios, namely the current ratio of 132%, Net Profit Margin of 5%, ROI of 7%, ROE of 19%, debt to Asset Ratio of 62%, and debt to Equity Ratio of 165%.